2016
DOI: 10.1007/s00412-016-0590-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair kinetics in SCID mice Sertoli cells and DNA-PKcs-deficient mouse embryonic fibroblasts

Abstract: Noncycling and terminally differentiated (TD) cells display differences in radiosensitivity and DNA damage response. Unlike other TD cells, Sertoli cells express a mixture of proliferation inducers and inhibitors in vivo and can reenter the cell cycle. Being in a G1-like cell cycle stage, TD Sertoli cells are expected to repair DSBs by the error-prone nonhomologous end-joining pathway (NHEJ). Recently, we have provided evidence for the involvement of Ku-dependent NHEJ in protecting testis cells from DNA damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Prior work has shown that Sertoli cells are reliant on the c-NHEJ pathway for DSB repair [35, 38]. Results here suggest that DSB repair is compromised in the Nono gt /0 Sertoli cells in vivo .…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…Prior work has shown that Sertoli cells are reliant on the c-NHEJ pathway for DSB repair [35, 38]. Results here suggest that DSB repair is compromised in the Nono gt /0 Sertoli cells in vivo .…”
Section: Discussionmentioning
confidence: 45%
“…Prior work has shown that 53BP1 is a more specific marker of DNA damage in the testes than γ-H2AX, which accumulates at programmed DSBs associated with meiosis in developing germ cells [35, 36]. The kinetics of 53BP1 foci formation have been characterized in cultured wild type and c-NHEJ deficient Sertoli cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work in mammalian cells has shown that the number of 53BP1 foci reaches a maximum at 30 min post-irradiation and declines thereafter ( 48 50 ). The number of residual foci at 4 h post-irradiation is significantly greater in c-NHEJ deficient cells than in their wild-type counterparts ( 51 ).…”
Section: Resultsmentioning
confidence: 99%